2014
DOI: 10.1007/s00109-014-1221-7
|View full text |Cite
|
Sign up to set email alerts
|

BCL2 protein signalling determines acute responses to neoadjuvant chemoradiotherapy in rectal cancer

Abstract: Modelling BCL2-family proteins identifies patients unresponsive to therapy. Caspase activation downstream of mitochondria cannot identify these patients. Rectal tumours of poor responders are BCL2- but not BCL-XL-dependent. DR_MOMP allows clinicians to identify patients who would not benefit from therapy. DR_MOMP is also a useful patient stratification tool for BCL2 antagonists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 40 publications
0
30
0
Order By: Relevance
“…With apoptosis converging on the BCL-2 family to execute the killing decision, understanding BCL-2 family proteins, their interactions and their context within other singling networks, will shed light on the effectiveness of chemotherapies and optimal combinations. The continued development of our BH3 profiling system and other biomarkers 116 (for instance, DR_ MOMP)117, 118, perhaps can help to provide guiding information in patient and drug selection in the future.…”
Section: In Conclusionmentioning
confidence: 99%
“…With apoptosis converging on the BCL-2 family to execute the killing decision, understanding BCL-2 family proteins, their interactions and their context within other singling networks, will shed light on the effectiveness of chemotherapies and optimal combinations. The continued development of our BH3 profiling system and other biomarkers 116 (for instance, DR_ MOMP)117, 118, perhaps can help to provide guiding information in patient and drug selection in the future.…”
Section: In Conclusionmentioning
confidence: 99%
“…The advantage of using such personalised dynamic models over static biomarkers, has already been demonstrated in several case studies (Fey et al, 2015;Flanagan et al, 2015;Murphy et al, 2013;Lindner et al, 2013). In contrast to previous approaches, the here proposed methodology is not restricted to models in which the total protein concentrations are time-invariant parameters.…”
Section: Discussionmentioning
confidence: 96%
“…Recently, multiple studies have shown that patient-specific differences in the dynamic behaviour of these signalling networks underlie individual pathogenetic changes and disease manifestation (Fey et al, 2015;Flanagan et al, 2015;Lindner et al, 2013;Murphy et al, 2013). For example, a dynamic model of the JNK pathway could predict the survival probabilities of cancer patients in neuroblastoma, a common childhood cancer (Fey et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The drug-induced priming changes correlate well with in vivo cytotoxicity. Others have used different methods for measuring the pretreatment apoptosis (23,24). The Prehn laboratory measures absolute protein levels of key BCL-2 family members in pretreatment samples.…”
Section: Pretreatment Apoptotic Parameters Predict Clinical Response mentioning
confidence: 99%